Development of Contextual Archipelago Insights E-Module to Increase Interest in Learning and Collaboration Skills - M. Farid Juan Nurfauzi Aziz; A. Rosyid Al Atok; Sri Untari (Inovasi Kurikulum, 2026)
The learning process cannot be separated from the tools in the form of teaching materials that assist teachers in carrying out teaching and learning. One of them is in Pancasila Education lessons, especially those related to the Archipelago Insight. The concept of the Archipelago Insight emerged from Indonesia's multicultural society. The condition of a multicultural society requires ideas that can guarantee unity and oneness in diversity. This study aims to develop an e-module for Archipelago Insight based on a contextual approach and to test its effectiveness in increasing students' interest in learning and collaboration skills among 9th-grade students at MTs Darun Najah Malang. This study uses the Research and Development (RnD) method with the ADDIE development model, which includes the stages of analysis, design, development, implementation, and evaluation. Data collection instruments used include an expert validation questionnaire, a learning interest questionnaire, and a collaboration ability observation sheet. The results of the expert validation indicate that the e-module is declared very feasible to use in terms of material, module structure, and language. The effectiveness test shows a significant increase in students' interest in learning. In addition, collaboration skills also increase. The Archipelago Insight e-module, grounded in a contextual approach, is effective in increasing students' interest in learning and in collaboration skills.   Abstrak Proses pembelajaran tidak dapat dipisahkan dari perangkat berupa bahan ajar yang membantu guru dalam melaksanakan pengajaran dan pembelajaran. Salah satunya adalah pada pelajaran Pendidikan Pancasila, khususnya yang berkaitan dengan Wawasan Nusantara. Konsep Wawasan Nusantara muncul dari masyarakat multikultural di Indonesia. Kondisi masyarakat multikultural membutuhkan gagasan yang mampu menjamin persatuan dan kesatuan dalam keberagaman. Penelitian ini bertujuan untuk mengembangkan e-modul Wawasan Nusantara berbasis pendekatan kontekstual serta menguji efektivitasnya dalam meningkatkan minat belajar dan kemampuan kolaborasi peserta didik kelas 9 MTs Darun Najah Malang. Penelitian ini menggunakan metode Research and Development (RnD) dengan model pengembangan ADDIE yang meliputi tahap analisis, desain, pengembangan, implementasi, dan evaluasi. Instrumen pengumpulan data yang digunakan meliputi angket validasi ahli, angket minat belajar, dan lembar observasi kemampuan kolaborasi. Hasil validasi ahli menunjukkan bahwa e-modul dinyatakan sangat layak digunakan pada aspek materi, struktur modul, dan kebahasaan. Uji efektivitas menunjukkan peningkatan signifikan pada minat belajar peserta didik. Selain itu, kemampuan kolaborasi juga meningkat. E-modul Wawasan Nusantara berbasis pendekatan kontekstual efektif dalam meningkatkan minat belajar dan kemampuan kolaborasi peserta didik. Kata Kunci: e-modul; kemampuan kolaborasi; minat belajar; pendekatan kontekstual; Wawasan Nusantara